Graphene-oxide-modified β-tricalcium phosphate bioceramics stimulate in vitro and in vivo osteogenesis. (November 2015) - Wu, Chengtie; Xia, Lunguo; Han, Pingping; Xu, Mengchi; Fang, Bing; Wang, Jiacheng; Chang, Jiang; Xiao, Yin
Abstract: Graphene oxide (GO) has attracted much interest for applications in bone tissue engineering; however, until now, the interaction between GO and stem cells, and the in vivo bone-forming ability of GO have not been explored. The aim of this study was to produce GO-modified β-tricalcium phosphate (β-TCP-GRA) bioceramics and then explore the material's osteogenic capacity in vitro and in vivo, as well as unravel some of the molecular mechanisms behind this. β-TCP-GRA disks and scaffolds were successfully prepared by a simple GO/water suspension soaking method in combination with heat treatment. These scaffolds were found to significantly enhance the proliferation, alkaline phosphatase activity, and osteogenic gene expression of human bone marrow stromal cells (hBMSCs), when compared with β-TCP without GO modification (controls). Activation of the Wnt/β-catenin signaling pathway in hBMSCs appears to be the mechanism behind this osteogenic induction by β-TCP-GRA. β-TCP-GRA scaffolds led to an increased rate of in vivo new bone formation compared to β-TCP controls, indicative of the stimulatory effect of GO on in vivo osteogenesis, making GO modification of β-TCP a very promising method for applications in bone tissue engineering, in particular for the regeneration of large bone defects.